"I Don't Have to Think About Watching the Ground": A Qualitative Study Exploring the Concept of Vigilance as an Important Outcome for Ankle Reconstruction. Issue 10 (29th September 2020) - Pinsker, Ellie B.; Sale, Joanna E. M.; Gignac, Monique A. M.; Daniels, Timothy R.; Beaton, Dorcas E.
Abstract : Objective: To understand patients' experiences of ankle reconstruction for treatment of end‐stage ankle osteoarthritis. Methods: Individuals were recruited from a cohort of individuals who had undergone total ankle replacement or ankle fusion. English‐speaking individuals who had surgery at least 1 year prior were invited to participate. Semistructured, face‐to‐face interviews relying on a phenomenological approach were conducted in a private hospital clinic room. Results: A total of 25 adults (12 women, 13 men), ages 25–82 years, were interviewed for 1–2 hours. Participants commonly described a state of having to keep careful watch for potential environmental challenges. Vigilance was related to ongoing symptoms (i.e., pain, stiffness) and concerns regarding balance, stability, and potential damage to the fused ankle or implant. Vigilance was described along a continuum, with higher levels associated with stress and mental exhaustion. Vigilance affected participants' perception of their surgical outcome, with high vigilance levels linked to negative perceptions of outcome. The degree to which individuals perceived the need for vigilance was influenced by environmental factors like uneven ground or crowds. Contrary to descriptions of vigilance in the coping literature, vigilance related to ankle reconstruction constituted a situational, rather than dispositional, response. Conclusion: Vigilance and its associated burden are not captured by current instruments. The mental load and worry associated with vigilance was important to patients, distinct from related pain or functional status. Thus, reducing high levels of vigilance appears to be an appropriate target for patient‐centered treatment outcomes. A thorough battery of outcome measures for ankle reconstruction should consider this domain.